Hubungan pengetahuan dengan sikap personal hygiene mengenai kesehatan reproduksi saat menstruasi pada remaja putri di wilayah kerja puskesmas air besar desa batu merah kota ambon - Adinda Zharifah Putri Satiawan; Hudi Winarso; Salmon Charles Siahaan (Bahasa Indonesia, 2023)
Personalihygiene is a method of care that is carried out in order to maintain physical and psychological health. How to provide an understanding of this with education, especially for young women. Youth means someone aged 12-19 years. Problems that occur in reproduction during adolescence have a physical impact and affect mental health, economic conditions and social welfare in the long term. There are several ways so that the reproductive organs are well cared for, commonly referred to as personal hygiene, namely the process of taking care of oneself so that they have good health, both physically and psychologically, especially in the reproductive organs. The purpose of this study was to determine the influence obtained between the knowledge and attitudes of young women and to find out whether this is applied to everyday life. This research is a non-experimental quantitative research using observationaI anaIytic research with the Cross Sectional method. This study consisted of 5 schools in the working area of ​​the Air Besar Community HeaIth Center with 90 subjects. The data coIIection instrument in this study was a questionnaire so that researchers know the relationship between knowIedge and attitudes regarding personal hygiene in young women during menstruation. The data used to analyze using the Chi Square statistical test. The resuIts of research conducted using the Chi-Square statisticaI test obtained a Continuity Correction value with a p-value of 0.011 less than the significance IeveI (0.05) so there is an influence between KnowIedge and Personal Hygiene Attitudes regarding reproductive health during menstruation in young women in the working area of ​​the Puskesmas Big Water of Batu Merah Village, Ambon City